Chronology of the western world, twentieth century - Erdoes, Richard; Society for Visual Education (Chicago, Ill. The Society [production company], 1984)
Presents a chronicle of the twentieth century. Examines the impact of wars, economic depression and the atomic bomb on the people of the world.
Keywords: History, Modern -- 20th century